2009
DOI: 10.1007/s10482-009-9388-6
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid and ursolic acid affect peptidoglycan metabolism in Listeria monocytogenes

Abstract: The plant pentacyclic triterpenoids, oleanolic and ursolic acids, inhibit the growth and survival of many bacteria, particularly Gram-positive species, including pathogenic ones. The effect of these compounds on the facultative human pathogen Listeria monocytogenes was examined. Both acids affected cell morphology and enhanced autolysis of the bacterial cells. Autolysis of isolated cell walls was inhibited by oleanolic acid, but the inhibitory activity of ursolic acid was less pronounced. Both compounds inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 31 publications
4
55
0
Order By: Relevance
“…The final study suggests the eventual stimulation of murein hydrolases [78] by OA can result in increased degradation of this macromolecule. A detailed study of the effects of OA and UA on peptidoglycan (murein) content, turnover and the autolysis of L. monocytogenes was published recently [79]. In this species, the causative agent of listeriosis is a facultative pathogen able to survive and multiply in macrophages [80].…”
Section: Cellular Targets and Functions Affected By Oa Ua And Their mentioning
confidence: 99%
“…The final study suggests the eventual stimulation of murein hydrolases [78] by OA can result in increased degradation of this macromolecule. A detailed study of the effects of OA and UA on peptidoglycan (murein) content, turnover and the autolysis of L. monocytogenes was published recently [79]. In this species, the causative agent of listeriosis is a facultative pathogen able to survive and multiply in macrophages [80].…”
Section: Cellular Targets and Functions Affected By Oa Ua And Their mentioning
confidence: 99%
“…Moreover, L. monocytogenes had lower OD values as oleanolic acid concentration increased (Tables 1-3). Inhibited growth of L. monocytogenes may be related to impaired peptidoglycan metabolism caused by oleanolic acid because the triterpenoids of oleanolic acid may influence the enzymes related to peptidoglycan metabolism such as the proteins involved in cell wall synthesis, hydrolysis and modification which might decrease peptidoglycan cross-linkage and thus enhance its susceptibility to mutanolysin, an N-acetylmuramidase (Kurek et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been reported that OA inhibited peptidoglycan metabolism in L. monocytogenes, resulting in the im-paired proliferation of the bacterial cells [10]. Therefore, it is necessary to examine if same mechanism applies to the case of S. mutans by OA addition.…”
Section: Resultsmentioning
confidence: 99%